Guide for the evaluation of qualitative research - Mireya Pérez; Francis Rietveldt (Telos: Revista de Estudios Interdisciplinarios en Ciencias Sociales, 2001)
The structuring of a guide to evaluate qualitative research arises from the concern over the lack of previously determined criteria that facilitate the correction of research work developed from that perspective.